2023
DOI: 10.1002/adtp.202200219
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polyester Nanoparticle Vaccines Deliver Self‐Amplifying mRNA in Mice at Low Doses

Abstract: Delivery of self-amplifying mRNA (SAM) has high potential for infectious disease vaccination due to its self-adjuvanting and dose-sparing properties. Yet a challenge is the susceptibility of SAM to degradation and the need for SAM to reach the cytosol fully intact to enable self-amplification. Lipid nanoparticles are successfully deployed at incredible speed for mRNA vaccination, but aspects such as cold storage, manufacturing, efficiency of delivery, and the therapeutic window can benefit from further improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…In this study we aimed to evaluate the effects of added polyanions to polycation/saRNA complexes, as prior studies had shown that mixed polycation/polyanion systems could transfect certain cancer cells in vitro and in vivo with greater efficacy for pDNA and with siRNA than the binary polycation nucleic acid complexes alone. 35 For assays with saRNA we made the specic choices of poly(b-amino-ester)s (PBAEs) as the polycations as these have been shown to be effective delivery agents for saRNA in pre-clinical studies, 36 and poly(glutamic acid)s (PGAs) owing to their known safety prole and ready availability. [37][38][39] The versatility of the routes to PBAEs and the ease of end-group modication via the nal capping stage has been exploited by many groups, with a range of chemistries adopted and with or without cell-targeting agents.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we aimed to evaluate the effects of added polyanions to polycation/saRNA complexes, as prior studies had shown that mixed polycation/polyanion systems could transfect certain cancer cells in vitro and in vivo with greater efficacy for pDNA and with siRNA than the binary polycation nucleic acid complexes alone. 35 For assays with saRNA we made the specic choices of poly(b-amino-ester)s (PBAEs) as the polycations as these have been shown to be effective delivery agents for saRNA in pre-clinical studies, 36 and poly(glutamic acid)s (PGAs) owing to their known safety prole and ready availability. [37][38][39] The versatility of the routes to PBAEs and the ease of end-group modication via the nal capping stage has been exploited by many groups, with a range of chemistries adopted and with or without cell-targeting agents.…”
Section: Discussionmentioning
confidence: 99%